The Aspects of Enogastronomic Culture of Forlì and Italian Language Learning: a Study with the Forliviamo app - Cervini, Cristiana; Zingaro, Anna (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
This paper aims to describe the development of the Forliviamo web application, which fosters incidental learning of Italian as L2 through the promotion of the city of Forlì and its surroundings. Following a brief portrayal of the context in which the app originated, the theoretical underpinnings that supported the project will be shortly outlined. Afterwards, a general description of the app contents and functions will be given. Particular attention will be paid to the contents related to local food and wine, which were the subject of a classroom testing with international students and whose outcomes will be analysed.